Financial Management Capacity, Accountability, Own Income Generation, Revenue Diversification and Financial Sustainability in Charities Of Malaysia - Cheuk, Sharon; Lian, Kee Phua; Siti Nabiha, A.K.; Salawati, Sahari; Nichol, Esmie O.; Michael, Tinggi (Universidad de Almería, 2020)
Malaysian charities have been reported to face problems in raising funds in the face of the current challenging economic environment. Some evidence has been provided by past research, in for-profit organisations, on the influence of accountability, financial management capacity, own income generation and revenue diversification on financial performance. This study examines their impact on non-profit financial sustainability, utilising as sample 212 active charities in 2017. The quantitative approach is adopted whereby data on financial management capacity, accountability, own income generation and revenue diversification, and their inter-relationships, were tested for strength and influence of the relationships, if any, with financial sustainability. Analysis of data was performed using the structural equation modeling method using lavaan on R. Global fit values (RMSEA = 0.00; SRMR = 0.04) showed a good model fit and standardised residuals justified retaining the model at the pairing levels of the observed variables; as such the original model is retained and not respecified. The findings suggest positive and significant indirect relationships between financial management capacity and accountability with the financial sustainability, as mediated by revenue diversification and own income generation. The implications and contributions arising from the findings are also discussed. Keywords: financial sustainability, financial management capacity, accountability, own income generation, revenue diversification, charities, Malaysia